Weird : the Al Yankovic story [videorecording (Blu-Ray + DVD)] - Appel, Eric, 1980-; Yankovic, Al, 1959-; Yankovic, Al, 1959-; Radcliffe, Daniel, 1989-; Wood, Evan Rachel, 1987-; Wilson, Rainn, 1966-; Huss, Toby, 1966-; Lancaster, Jack (Actor); Clark, Spencer Treat, 1987-; O'Brien, Tommy (Actor); Castro, Arturo, 1985-; Nicholson, Julianne, 1971-; et al. (Shout! Studios, a division of Shout! Factory, LLC, 2023)
From a conventional upbringing where playing the accordion was a sin, Al Yankovic rebelled and made his dream of changing the words to world-renowned songs come true. An instant success and sex symbol, Al lives an excessive lifestyle and pursues an infamous romance that nearly destroys him.